2021
DOI: 10.1021/acs.biochem.1c00467
|View full text |Cite
|
Sign up to set email alerts
|

Long Tracts of Guanines Drive Aggregation of RNA G-Quadruplexes in the Presence of Spermine

Abstract: G-Quadruplexes (GQs) are compact, stable structures in DNA and RNA comprised of two or more tiers of quartets whose G-rich motif of tracts of two or more G's occurs commonly within genomes and transcriptomes. While thermodynamically stable in vitro, these structures remain difficult to study in vivo. One approach to understanding GQ in vivo behavior is to test whether conditions and molecules found in cells facilitate their folding. Polyamines are biogenic polycations that interact with RNA. Among common polya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 68 publications
3
19
0
Order By: Relevance
“…Such condensates would likely be associated with high divalent and organic cation concentrations on the basis of our findings with riboswitches (Poudyal et al in press) and Gquadruplexes (Williams et al 2021). Nonetheless, proteins play critical roles in condensate formation and properties.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Such condensates would likely be associated with high divalent and organic cation concentrations on the basis of our findings with riboswitches (Poudyal et al in press) and Gquadruplexes (Williams et al 2021). Nonetheless, proteins play critical roles in condensate formation and properties.…”
Section: Discussionsupporting
confidence: 50%
“…Removal of salt stress (Tack et al 2020) would relieve conventional RNA-RNA base pairing interactions, which are favored by high salt, which might also dissolve condensates. On other hand, we have found that aggregates of spermine-promoted Gquadruplexes are eliminated by higher salt (Williams et al 2021), which is the opposite effect, occurring here because the salt competes the spermine away from the RNA. The major takeaway from these studies is that abiotic variables such as temperature and salt can have a multitude of effects on biomolecular condensates such that their dynamics, especially in living systems.…”
Section: Disruptive Forces For Phase Separationmentioning
confidence: 71%
See 1 more Smart Citation
“…Therefore, the rigidity and charge density of an aptamer are greater than those of the double-stranded DNA, and liquid–solid phase separation occurs when the aptamer is mixed with PLL under the studied conditions. A similar result was obtained when the dense G-quadruplex was mixed with polycations …”
Section: Resultsmentioning
confidence: 90%
“…The stacking/clustering should involve stacking between RNA single-stranded regions [23] or stacking between multiple nucleobases. [24] To map the location-specific RNA structure in the condensed phase, we employed SRM [13a] and collected a hyperspectral stack of Raman images at wavelengths from 650 to 1600 cm -1 for the three types of RNA droplets. After normalizing by the Raman intensity at 1100cm -1 , the intensity differences at other wavelengths become obvious (Figure S5).…”
mentioning
confidence: 99%